Urban Road Networks and Ecological Sustainability in Dense Settlements: A Qualitative Study - Fajar Affanul Hakim (Program Studi Arsitektur, Fakultas Teknik, Universitas Katolik Parahyangan, 2026)
Urban road network development, particularly along the Pembangunan Andara and Andara Raya segments, has driven significant land-use change and increased carbon-emitting activities. This study examines the ecological implications of such development at the street-segment scale within dense settlements. A descriptive qualitative approach combining field observation and spatial analysis was applied. The findings reveal that 28.57% of the study area experienced high-contrast land-use transformation, resulting in reduced green space and the formation of 17 connectivity routes that intensify socio-economic activities and carbon emissions. These results indicate that current planning approaches remain predominantly mobility-oriented and insufficiently integrate ecological considerations. This study proposes an ecological-based analytical framework that emphasizes green zones as carbon absorbers, noise buffers, and microclimate regulators—elements not yet explicitly addressed in existing regulations. Additionally, the integration of sustainable tactical urbanism is identified as a potential strategy to support low-carbon socio-economic interactions at the local scale.